Determining The Service Quality Framework For Halal Food Industry - Al-Kendi, Khaled Ahmed (2012)
This exploratory study is to determine the service quality framework for Halal food industry,by examining a hypothesized model which postulated the relationships between six determinants of Halal Service Quality and Behaviour intention to purchase.The six determinants were then tested against Behavior Intention to complete the Halal Service Quality Framework.